The clinicopathological spectrum and management of intraductal papillary mucinous neoplasm of the bile duct (IPMN-B). (April 2013) - D'souza, Melroy A; Isaksson, Bengt; Löhr, Matthias; Enochsson, Lars; Swahn, Fredrik; Lundell, Lars; Arnelo, Urban
Abstract Background. Intraductal papillary mucinous neoplasm of the bile duct (IPMN-B) is a rare but increasingly diagnosed clinical entity. Typical cholangioscopic findings usually include intraductal protruding papillary tumors that secrete mucus. Methods. Clinical, radiological and histopathological data of seven consecutive patients who were found to have IPMN-B were analyzed. Results. Six of the seven patients presented with obstructive jaundice/cholangitis as the presenting complaint. ERCP and other imaging were equivocal in five of these patients and peroral cholangioscopy (POCS, single-operator cholangioscopy system) was performed. This revealed mucin-producing intraductal tumors with numerous frond-like papillary projections; a macroscopic appearance consistent with IPMN-B. Preoperative biopsy revealed adenoma, with low-grade dysplasia in two patients and high-grade dysplasia in three. Three patients underwent Whipple resection; one underwent total pancreatectomy with left hepatectomy, one patient a pancreas preserving duodenectomy with common bile duct reimplantation and one patient an extended right hepatectomy. These patients were found to have IPMN-B with adenomatous changes with varying grades of dysplasia and even cholangiocarcinoma on final histopathology. One patient first underwent endoscopic papillectomy and on follow-up was found to have cholangiocarcinoma with metastases to the liver. Conclusion. POCS can be a key diagnostic investigation in the evaluation of patients with papillary tumors of the bile duct. IPMN-B has a heterogenous pathology and varying grades of dysplasia and even carcinoma may exist in the same patient. Surgical management should be radical and based on tumor extent.